Electricity, Electronics, and Wiring Diagrams for HVAC/R - MAHOVEV, Edward F (PRENTICE HALL, 2006)
This book provides a comprehensive but simple review of electricity and electronics along with the coverage of many circuits and wiring diagrams of operating HVAC/R systems. Gives technicians in the field of modern HVAC/R all they need to be successful. Published in two main sections, the first section covers basic electricity and basic electronics related to the needs of air conditioning refrigeration technicians, while the second section of the book covers practical circuits and systems. For HVAC/R Technicians.